Distribution of Nickel in Different Phases of Soil Samples and Plant Parts Taken From Serpentine and Copper Mining Area - Kaplan, Olcay; Yaman, Mehmet; Kaya, Gokce (Asian Journal of Chemistry, 2010)
Speciation is important to determine the mobility, bioavailability and/or toxicity of trace elements in soils because the total metal concentrations are not adequate for determination of these properties. In this study, four stage sequential extraction procedures were used to determine different Ni phases in soil samples. Soil samples and plants grown in these soils were collected from serpentine and copper-mining area in Maden-Elazig-Turkey. The extracted fractions are: exchangeable/carbonate, reducible-iron/manganese oxides, oxidizable-organic matter and sulfides and residual except silicates. In addition, selective extraction procedures were applied to the same samples and the results were compared. The concentrations of Ni in soil and plant samples were determined by flame atomic absorption spectrometry (FAAS) and inductively coupled plasma-mass spectrometry (ICP-MS). Considerable Ni concentrations in hydroxylamine hydrochloride extracts were found compared to other selective extracts. Because of translocation factor higher than 1, Rumex (Sorrel) leaves can be used as hyperaccumulator.